GENERAL AND SPECIFIC COMBINING ABILITY OF MAIZE TRAITS STUDIED IN SINGLE CROSS HYBRIDS - & Hussen, Hussain (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The study was carried out using full diallel cross between six inbred lines of maize, parents and their F1 including reciprocals were planted in 19th march 2014 at field of agriculture college, Duhok University. All treatments arranged in randomized complete block design (RCBD) with three replications to estimate the general and specific combining ability of maize traits in single cross hybrids. According to the mean square values of The results showed that the general combining ability, specific combining ability, and reciprocal combining ability, the general combining ability exhibited significant variance for all traits except days to 75% tasseling and number of kernels row-1, whereas, specific combining ability was non significant for leaf area though its prerogative for all other traits. The reciprocal combining ability was remarkable for days to 75% tasseling, plant and ear height, leaf area, ear diameter, ear length, number of rows ear-1, number of kernels row-1, 300- kernel weight and yield plant-1. The hybrid IK8xTH613 displayed the best value for yield plant-1 and IK58XTH613 for days to 75% tasseling, while the reciprocal HSxIK8 was the best for yield plant-1.